LEGAL ANALYSIS REGARDING EVIDENCE IN ONLINE BALLS GAMBLING CRIME: ANALISIS HUKUM TENTANG PEMBUKTIAN DALAM TINDAK PIDANA PERJUDIAN BOLA ONLINE - Lihara, Mohd Fariz (LPPM UPMI, 2023)
Online gambling is a game that is carried out using money as a bet with the terms of the game and the amount of bets determined by online gamblers and using electronic media with internet access as an intermediary. One example of online gambling that is popular with today's society, namely online soccer gambling. This research method uses qualitative methods with a library approach. This study aims to examine how legal evidence is involved in criminal acts related to online soccer gambling cases. The results of this study state that online gambling law enforcement uses the instrument Article 303 of the Criminal Code (KUHP) instead of Article 27 paragraph (2) Jo. Article 45 of the Information Technology and Electronics Law (UU ITE). The threat of imprisonment under Article 303 of the Criminal Code is 10 years, heavier than Article 27 (2) Jo. Article 45 Law on Information Technology and Electronics.